Possible Effects of European Monetary Union on Switzerland : A Case Study of Policy Dilemmas Caused by Low Inflation and the Nominal Interest Rate Floor - Laxton, Douglas; Prasad, Eswar (Washington, D.C. : International Monetary Fund, 1997)
This paper examines the possible effects on Switzerland of asset preference shifts in favor of Swiss-franc-denominated assets that could result from EMU. Alternative policy responses to temporary and persistent asset preference shifts and the consequent pressures for exchange rate appreciation are examined. Simulations of a stylized macroeconomic model of the Swiss economy indicate that monetary policy is likely to be the most effective tool for stabilizing output in the short run, but at the cost of a temporary increase in inflationary pressures. The simulations highlight the dilemmas faced by policymakers in an environment with low inflation and nominal interest rates.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet